2018
DOI: 10.1093/isr/viy044
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing Collective Trauma in International Political Economy

Abstract: While existing literature on collective trauma in international relations represents a vital (albeit inchoate) contribution to the field, to date, it has largely analyzed collective trauma’s impact as primarily psychological and sociocultural. This essay argues that a complete vision of collective trauma in IR must incorporate not only these more intangible dimensions but also how its legacy is reified materially over time in economic conditions—distinguishing the trauma of those with the resources to “work th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…To navigate such challenges, some positivist IPE studies have built on economist Herbert Simon's (1997) notion of "bounded rationality" to take "into account the cognitive limitations of the decision maker, limitations of both knowledge and computational capacity" (e.g., Odell 2002;Poulsen 2015). However, what has been a largely separate camp of IPE research investigates a ect, anxiety, resilience, trauma, and other human emotions (Brassett 2018;Brassett and Vaughan-Williams 2012;Da Costa 2016;Lerner 2019;Widmaier 2010). It is these latter studies that shift from knowledge/information toward power/knowledge.…”
Section: Situating and Destabilizing Knowledge About Subjective And C...mentioning
confidence: 99%
“…To navigate such challenges, some positivist IPE studies have built on economist Herbert Simon's (1997) notion of "bounded rationality" to take "into account the cognitive limitations of the decision maker, limitations of both knowledge and computational capacity" (e.g., Odell 2002;Poulsen 2015). However, what has been a largely separate camp of IPE research investigates a ect, anxiety, resilience, trauma, and other human emotions (Brassett 2018;Brassett and Vaughan-Williams 2012;Da Costa 2016;Lerner 2019;Widmaier 2010). It is these latter studies that shift from knowledge/information toward power/knowledge.…”
Section: Situating and Destabilizing Knowledge About Subjective And C...mentioning
confidence: 99%
“…They carry the burden of the “guardianship” of a traumatic generational past (Hirsch, 2008: 104). These collective traumas constitute “a social, interpersonal phenomenon, which, when narrated into national identity, can constitute the nation-state’s identity” and influence its activities (Lerner, 2019: 563).…”
Section: Postmemory Eritrea’s Chosen Trauma and The Second-generation Diasporamentioning
confidence: 99%
“…The passing of memories, be they actually lived memories or parts of a constructed collective memory, is a process that produces certain states of mind and political opinions that can influence the further course of history (Lerner, 2019: 550). Matthies-Boon and Head (2018) found that authoritarian governments are not only creating individual trauma such as PTSD, but also social and political trauma: “The social trauma occurring in repressive authoritarian societies […] occurs due to the restriction of communicative spaces and the strategic deconstruction of potential forms of social and collective flourishing” (2018: 262).…”
Section: Postmemory the Government Of Eritrea And The Legacy Of The Martyrsmentioning
confidence: 99%
“…Still, the relationship between underlying experiences of psychic trauma, present in many interconnected individuals, and a collective victimhood nationalism is not linear. Ample scholarship has pointed out that trauma’s legacy on a political culture is determined not only by the severity of the precipitating offence, but also by the way in which it is embedded in sociocultural environments and material circumstances, the potency of its narration, public efforts to mourn and ‘work through’ the shock, 8 and the resources available for rehabilitation (Lerner, 2018b). This section explores how paradox is inherent to theorizing collective trauma and how this paradox implies tension between underlying psychological trauma and the narratives that emerge to represent and politicize it.…”
Section: Defining Victimhood Nationalismmentioning
confidence: 99%
“… 7. For more on the distinction between different ontological approaches to collective trauma and its identity narratives, see Lerner (2018b). …”
mentioning
confidence: 99%